The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1088/1402-4896/abf67b
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biomagnetic blood flow in a stenosed bifurcation artery amidst elastic walls

Abstract: In recent years, fluid-structure interaction (FSI) analysis has generated remarkable interest of researchers in interdisciplinary sciences problems, for instance, mechanical engineering, biomedical engineering, i.e., incorporating elastic wall behaviour in human arteries. Here, in this paper, we considered incompressible Newtonian blood flow and the elastic bifurcated artery wall in a non-uniform magnetic field. The considered model of Biomagnetic Fluid Dynamics (BFD) describes both magnetization and electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Physically this mean for shear thinning blood the velocity profile of the fluid is maximum and for shear thickening blood flow velocity decreases and exert pressure on the walls of the artery. Also for n = 1 the results are matched for the viscus case discussed by Anwar et al 26 Also near the stenosis velocity is maximum. In order to get an insight of the velocity behavior before and after the stenosis the findings between the points A and B is focused and are displayed in Figs.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Physically this mean for shear thinning blood the velocity profile of the fluid is maximum and for shear thickening blood flow velocity decreases and exert pressure on the walls of the artery. Also for n = 1 the results are matched for the viscus case discussed by Anwar et al 26 Also near the stenosis velocity is maximum. In order to get an insight of the velocity behavior before and after the stenosis the findings between the points A and B is focused and are displayed in Figs.…”
Section: Resultsmentioning
confidence: 60%
“…Further we assumed the walls are made up of isotropic and linearly elastic material having specific Poisson ratio and Young’s modulus. Which are defined as follows where = Lame coefficient, = Shear modulus, = Young’s Modulus, = Poisson ratio.where and value of 26 .
Figure 1 schematic diagram of the problem (left) and coarse mesh (right).
…”
Section: Geometry Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Once grid independence is established, the validation of code is presented against the results of Anwar et al 42 for contour plots and velocity magnitude and are shown in Fig. 2 and Table 2 respectively.…”
Section: Problem Setupmentioning
confidence: 99%
“…The comparison demonstrated the accuracy of our results, and a good agreement among the respective results is obtained, which ensures that the results obtained from the present study are reliable for accuracy check.
Figure 2 Comparison for the contour plots at , Anwar et al 42 (left) and present (right).
…”
Section: Problem Setupmentioning
confidence: 99%